2014
DOI: 10.1089/acm.2014.0177
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Treatment for Anxiety: A Systematic Review of Human Trial Results Reported for the Ayurvedic Herb Ashwagandha (Withania somnifera)

Abstract: Objective: To assess existing reported human trials of Withania somnifera (WS; common name, ashwagandha) for the treatment of anxiety. Design: Systematic review of the literature, with searches conducted in PubMed, SCOPUS, CINAHL, and Google Scholar by a medical librarian. Additionally, the reference lists of studies identified in these databases were searched by a research assistant, and queries were conducted in the AYUSH Research Portal. Search terms included ''ashwagandha,'' ''Withania somnifera,'' and ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(50 citation statements)
references
References 18 publications
2
42
0
6
Order By: Relevance
“…In human studies, a recent systematic review by Pratte, Nanavati, Young, and Morley (2014) discussed previous studies of ashwagandha on anxiety/stress outcomes. They identified five human RCTs with 400 participants.…”
Section: Withania Somnifera (Ashwagandha)mentioning
confidence: 99%
“…In human studies, a recent systematic review by Pratte, Nanavati, Young, and Morley (2014) discussed previous studies of ashwagandha on anxiety/stress outcomes. They identified five human RCTs with 400 participants.…”
Section: Withania Somnifera (Ashwagandha)mentioning
confidence: 99%
“…In human studies, a recent systematic review (Pratte, Nanavati, Young, & Morley, 2014) captured all previous studies of W. somnifera with anxiety/stress outcomes (e.g., Auddy et al, 2008;Chandrasekhar et al, 2012;Chengappa et al, 2013). This identified five human RCTs with 400 participants (range = 39-130).…”
Section: Valeriana Officinalis (Valerian)mentioning
confidence: 99%
“…One of the constituents of Adaptra Ā® Forte, Withania somnifera, is reported to be effective in the treatment of anxiety. According to [46], five clinical studies concluded that W. somnifera intervention resulted in greater score improvements (significantly, in most cases) than placebo in outcomes on anxiety or stress scales. Broad evidence from preclinical studies indicates a possible anxiolytic and/or anti-depressive activity of constituents from W. somnifera [26,47].…”
Section: Discussionmentioning
confidence: 99%